2011
DOI: 10.1097/bot.0b013e31821ac6e3
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Role of the Orthopaedic Surgeon in Management of Fragility Fractures?

Abstract: Fragility fractures are the most prevalent trauma condition that orthopaedic surgeons face today. Osteoporosis and susceptibility to falls are the key predisposing factors. Despite evidence supporting the impact of treating osteoporosis on reducing the incidence of fragility fractures, it is often left untreated. Orthopaedic surgeons are often the first physicians to assess and treat the patient after a fragility fracture. Their role therefore does not end in the skillful fixation of the fractures, but they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Multiple studies have suggested algorithms to combat this phenomenon. [34][35][36][37][38][39] Although osteoporosis rates are now at pandemic proportions, few studies exist in the orthopedic and neurosurgical literature describing osteoporosis prevalence based on BMD measurements in patients presenting with musculoskeletal complaints other than fracture. One study of 500 general orthopedic outpatients whose mean age was 67 years quantified BMD with calcaneal quantitative ultrasound and found that 31% had abnormal BMD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have suggested algorithms to combat this phenomenon. [34][35][36][37][38][39] Although osteoporosis rates are now at pandemic proportions, few studies exist in the orthopedic and neurosurgical literature describing osteoporosis prevalence based on BMD measurements in patients presenting with musculoskeletal complaints other than fracture. One study of 500 general orthopedic outpatients whose mean age was 67 years quantified BMD with calcaneal quantitative ultrasound and found that 31% had abnormal BMD.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective randomized trial found that compared with ''usual'' care, patients were twice as likely to be taking treatment for OSP management six months following fracture if it was initiated by the attending orthopaedic surgeon with follow-up in a dedicated orthopaedic OSP clinic [45]. Fracture care by the orthopaedic surgeon should be followed by efforts to prevent subsequent fracture such as a falls prevention assessment, an exercise programme to improve muscle tone and strength and commencement of bone protective therapy with BMD assessment by DXA for risk stratification and provision of a baseline to guide therapy [46]. While some of these interventions may be outside the skill-set of most orthopaedic surgeons they are easily accessible by referral to rheumatology, endocrinology or geriatric medicine colleagues who have an interest in bone disease.…”
Section: Secondary Fracture Preventionmentioning
confidence: 99%